Transformational leadership and corporate entrepreneurship: Cross-level mediation moderation evidence. Issue 6 (7th August 2017) - Chang, Yi-Ying; Chang, Che-Yuan; Chen, Chung-Wen
Abstract : Purpose: The purpose of this paper is to examine how transformational leadership may relate to corporate entrepreneurship by adopting a multilevel approach. The authors also theorized and tested the top-down and bottom-up intermediate process linking transformational leadership and corporate entrepreneurship. Design/methodology/approach: Multisource data across different timeframes were collected from 129 managers and 244 employees from 55 units of 27 firms. Findings: The results showed that transformational leadership and corporate entrepreneurship were positively related at the unit level. Furthermore, unit-level collective efficacy mediated the relationship between unit-level transformational leadership and unit-level corporate entrepreneurship. The authors also found that the firm-level empowerment climate moderated the indirect effect of unit-level collective efficacy on the relationship between unit transformational leadership and unit-level corporate entrepreneurship. Originality/value: First, the goal of this study is to extend the single focus of transformational leadership on corporate entrepreneurship (e.g. Ling et al., 2008) and develop a more thoughtful approach on determining how transformational leaders influence corporate entrepreneurship across levels. This study responds to calls for research to look at the impact of unit-level transformational leaders, such as middle managers, across levels (Ren and Guo, 2011) and creates a multilevel framework in which transformational leaders at the unit level influence the appearance of corporate entrepreneurship at the unit level.